Nonstationarities of postural sway. - Loughlin, P.J.
Time-frequency analysis of visually induced postural sway has uncovered potentially important time-dependent spectral changes in sway, particularly over intervals shorter than most trial lengths (tens of seconds). Specifically, our studies of center of pressure (COP) in response to sinusoidal (0.25 Hz) moving scene perturbations demonstrate that there are significant population-dependent time-varying changes in response to such visual perturbations, manifest in the instantaneous power at the stimulus frequency, and in low-order conditional moments of the time-varying spectral density of sway (the conditional mean frequency and bandwidth, also called the instantaneous frequency and the instantaneous bandwidth). In particular, adaptation, as quantified by a decrease in the instantaneous power of sway over time at the stimulus frequency, was observed in the control and elderly subjects but not in the vestibularly impaired group. We believe that these quantities are important measures for studying time-variations in postural sway and that continued application of nonstationary analysis methods such as time-frequency analysis is necessary to better understand and model time-varying aspects of balance.
Keywords: 0.25 Hz; Adaptation; Bandwidth; Center of pressure; Conditional mean frequency; Control subjects; Healthy elderly subjects; Healthy young subjects; Human balance; Instantaneous bandwidth; Instantaneous frequency; Low-order conditional moments; Nonstationary analysis; Population-dependent time-varying changes; Postural sway nonstationarities; Sinusoidal moving scene perturbations; Stimulus frequency; Time-dependent spectral changes; Time-frequency analysis; Time-variations.; Vestibularly impaired group; Visual perturbations; Visually induced postural sway